The numbers in the words of Muhammad, may God bless him and grant him peace, are examples and reflections: نماذجُ وتأملات (Journal of Academic Research, 2024)
The Prophetic discourse is distinguished by numerous characteristics and unique features. Consequently, scholars have devoted considerable attention and care to its words, meticulously documenting the noble Prophetic traditions and deriving legal rulings from them.One notable aspect observed in the Hadiths of the Prophet ﷺ is his use of numbers and numerical expressions in speech, particularly smaller numbers such as two, three, four, five, six, and seven.In this study, I have highlighted the most significant features of Prophetic discourse and emphasized the importance of numerical references within Prophetic speech. Furthermore, I compiled a selection of Prophetic Hadiths that include mentions of numbers, providing reflections and observations on these numerical references.The study concludes with several findings, the most important of which are:1. The speech of the Prophet ﷺ is characterized by profound qualities and remarkable traits.2. Numerical references in Prophetic discourse play a significant role in capturing the listener's attention, sparking curiosity about the content associated with the numbers, encouraging the pursuit of understanding, and simplifying concepts for the audience. This approach effectively stimulates their interest and emotions.3. The numbers mentioned in the Hadiths encompass a wide range of religious topics, including matters of the unseen, Prophetic narratives, encouragement and deterrence, legal rulings, and more.4. These numerical references often group similar items to provoke intellectual reflection and to explore connections and similarities between them.The study recommends the following:• Raising awareness about the importance of the Prophetic Sunnah and educating younger generations on emulating the Prophet ﷺ in his speech and methods of calling to Allah, persuasion, and effective communication.• Encouraging relevant institutions to organize scientific seminars that focus on Prophetic discourse and extract its benefits in various fields.• Motivating scholars and students of knowledge to author works on the role of numbers in Prophetic discourse, clarifying their purposes and objectives, and demonstrating their impact on listeners